2012
DOI: 10.17221/786/2011-pse
|View full text |Cite
|
Sign up to set email alerts
|

Biological nitrogen fixation of Biserrula pelecinus L. under water deficit

Abstract: The present work studied the effects of water deficiency conditions on the biological nitrogen fixation of three native rhizobia (SafPt12, SafPt6, and AjuPt16) isolated from Biserrula pelecinus L., and a reference strain Mesorhizobium ciceri biovar biserrulae. In terms of plant-water status, B. pelecinus showed typical signs of drought avoidance strategies such as reducing the aboveground development (i.e. reduction in leaf surface area and increase in root/ shoot ratio) in detriment of a better developed root… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…B iserrula pelecinus is a semi‐erect, self‐regenerating annual legume originating from the southern Mediterranean . Its desirable characteristics include high seed production, adaptation to a broad range of soil types, a deep root system and grazing tolerance, and these result in a highly productive pasture that is more drought resistant and shows greater self‐regeneration compared with other pasture legumes . Biserrula was first developed for agricultural use in Western Australia during the 1990s and varieties have since been introduced into a number of areas of New South Wales.…”
mentioning
confidence: 99%
“…B iserrula pelecinus is a semi‐erect, self‐regenerating annual legume originating from the southern Mediterranean . Its desirable characteristics include high seed production, adaptation to a broad range of soil types, a deep root system and grazing tolerance, and these result in a highly productive pasture that is more drought resistant and shows greater self‐regeneration compared with other pasture legumes . Biserrula was first developed for agricultural use in Western Australia during the 1990s and varieties have since been introduced into a number of areas of New South Wales.…”
mentioning
confidence: 99%
“…; Vicente et al. ), the lack of treatment effects on either tissue N or δ 15 N does not suggest an increase in water stress on Rhizobium with increasing precipitation variability.…”
Section: Discussionmentioning
confidence: 92%
“…In Ornithopus, the rhizo-symbiotic nitrogen acquisition pattern, typical for legumes, was evident from the significantly lower tissue d 15 N, as compared to Rumex, Tolpis, and Agrostis, and the significantly higher tissue N, as compared to all other species. However, although studies have shown that N 2 fixation in legumes is sensitive to moisture deficiency (e.g., Serraj et al 1999;Vicente et al 2012), the lack of treatment effects on either tissue N or d 15 N does not suggest an increase in water stress on Rhizobium with increasing precipitation variability.…”
Section: Species-specific Adaptation Strategies -The Legume Ornithopumentioning
confidence: 96%
“…Relatively few isolates were considered to efficiently fix N, emphasising the extremely specific relationship between B. pelecinus and its micro-symbiont (Howieson et al 1995;Nandasena et al 2004). The B-value, δ 15 N from N 2 fixing-plant when totally dependent on N 2 as the only N source, was determined as −3.53‰ (Vicente 2010) and the N dfa (the fraction of N derived entirely from N 2 fixation) estimated from the more efficient B. pelecinus root-nodule bacteria ranged between 67% and 73%. The difference between δ 15 N in the reference crop (δ 15 N ref = 7.16‰) and B-value (δ 15 N = −3.53‰) was more than five δ 15 N units, ensuring the other precondition for NA application (Högberg 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The B-value used was −3.53‰ calculated elsewhere (Vicente 2010). The total amount of N in the plant derived from N 2 fixation (N fix ) was determined by N fix = N dfa × N content.…”
Section: Methodsmentioning
confidence: 99%